THE UTILIZATION OF CYBER EXTENSION BY FISH FARMER IN KOTO MESJID VILLAGES OF XIII KOTO KAMPAR SUBDISTRICT KAMPAR REGENCY RIAU PROVINCE - Nazhif Arrahman; Zulkarnain '; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in February 2017 in Koto Mesjid Village, Kampar Regency, Riau Province. The selection of the location of this research is done deliberately because the village of Koto Mesjid is an area that most of the fish farmers and almost every house has Wi-Fi access so that this village also bears the title of